Liquid film rupture beyond the thin-film equation: A multi-component lattice Boltzmann study - Pelusi, F.; Sega, M.; Harting, Jens (Physics of Fluids, 2022)
Under the condition of partial surface wettability, thin liquid films can be destabilized by small perturbations and rupture into droplets. As successfully predicted by the thin film equation (TFE), the rupture dynamics are dictated by the liquid-solid interaction. The theory describes the latter using the disjoining pressure or, equivalently, the contact angle. The introduction of a secondary fluid can lead to a richer phenomenology, thanks to the presence of different fluid/surface interaction energies but has so far not been investigated. In this work, we study the rupture of liquid films with different heights immersed in a secondary fluid using a multi-component lattice Boltzmann (LB) approach. We investigate a wide range of surface interaction energies, equilibrium contact angles, and film thicknesses. We found that the rupture time can differ by about one order of magnitude for identical equilibrium contact angles but different surface free energies. Interestingly, the TFE describes the observed breakup dynamics qualitatively well, up to equilibrium contact angles as large as 130 . A small film thickness is a much stricter requirement for the validity of the TFE, and agreement with LB results is found only for ratios epsilon = h / L of the film height h and lateral system size L, such as epsilon <= x 10(-3).
CRIS-Team WoS Importer:2022-07-01